Práticas de gestão ambiental voltadas à logística reversa de embalagens na indústria vinícola - Gugel, Gisele Mion (My University, 2020)
Reverse logistic of packages is a relevant issue on the current context, especially after the approval of the National Solid Waste Policy - NSWP, established by Law No. 12.305/2010. Tied to the concept of sustainability, all the actors involved on the supply chain have a common responsibility of the management and correct distribution of waste generated. In Brazil, the vitiviniculture is concentrated in Rio Grande do Sul, more specifically in the Serra Gaúcha, nevertheless, there isn’t a defined reverse logistic chain, that fulfils effectively the national legislation. The territory of Vale dos Vinhedos is in that region and it was the first geographic indication recognized in the country, therefore, it became a reference for the national vitiviniculture field. The wine industry traditionally use glass package in your productive process, thus, generated a large amount of this disposal after the consume, because the bottle its use just one time, also employed plastic, paper and metal. Thus, this work proposed identify the practices of environmental management towards to reverse logistic of after-use packages, followed by wineries located in Vale dos Vinhedos and associated to Aprovale – Associação dos Produtores de Vinhos Finos do Vale dos Vinhedos. Through library research it was explored the concepts of sustainability, environmental management and reverse logistic, beside the interlinked these concepts between them and with the NSWP. To clear understand the flow of reverse logistic of package from the vitiviniculture, it was decided outline a generic model of wine supply chain, based on literature. Afterwards, has been produced a questionnaire to verifind which practices of environmental management and reverse logistic are adopted by the corporations. Thereafter, it was carry out a study of multiples cases in the wineries industries on the defined region, with the application of the structured questionnaire, characterize this study how exploratory and quali-quantitative approach. It were analyzed six companies, identified like V1, V2, V3, V4, V5 and V6. The review the results prove that all the wineries have the environmental licence and the SRMP - Solid Residues Management Plan - updated, how is indicated on the legislation. The results showed that the companies not realise campaigns from the awareness of the consumers, as well as does not having initiative to do the installation of collection points or agreements with suppliers for gather the after-use packages. The reverse logistic of packages its observed just on companie V4, by the way, it's the only one thats have investments in cooperatives and associations of recyclable material collectors. Based on these data, it was suggested the implementation of a reverse logistic system that involve the consumers, in compliance with current legislation.
A logística reversa de embalagens é um assunto relevante no contexto atual, especialmente após a aprovação da Política Nacional de Resíduos Sólidos - PNRS, instituída pela Lei nº 12.305/2010. Atrelado ao conceito da sustentabilidade, todos os envolvidos na cadeia de suprimentos passam a ter responsabilidade compartilhada sobre a gestão e destinação adequadas dos resíduos gerados. No Brasil, a vitivinicultura concentra-se no Rio Grande do Sul, com destaque para a Serra Gaúcha, e não possui uma cadeia de logística reversa definida e que cumpra efetivamente a legislação nacional. O território do Vale dos Vinhedos está inserido nesta região e foi a primeira indicação geográfica reconhecida do país, sendo referência para o setor vitivinícola nacional. A indústria vinícola tradicionalmente utiliza embalagens de vidro em seu processo produtivo, gerando uma grande quantidade de descarte pós-consumo deste resíduo, por ser de uso único, além de plástico, papel e metal. Nesse contexto, buscou-se identificar as práticas de gestão ambiental voltadas à logística reversa de embalagens pós-consumo adotadas pelas vinícolas localizadas no Vale dos Vinhedos e associadas à Aprovale – Associação dos Produtores de Vinhos Finos do Vale dos Vinhedos. Por meio de pesquisa bibliográfica foram explorados os conceitos de sustentabilidade, gestão ambiental e logística reversa, além da interligação destes conceitos entre si e com a PNRS. Para uma melhor compreensão dos fluxos da logística reversa de embalagens no setor vitivinícola, optou-se por delinear um modelo genérico de cadeia de suprimentos na indústria vinícola, com base na literatura. Após esta etapa, elaborou-se um questionário para verificar quais as práticas de gestão ambiental e de logística reversa são adotadas pelas empresas. Na sequência, realizou-se um estudo de casos múltiplos nas indústrias vinícolas da região delimitada, com a aplicação do questionário estruturado, caracterizando este estudo como exploratório com abordagem quali-quantitativa. Foram analisadas seis empresas, identificadas como V1, V2, V3, V4, V5 e V6. A análise dos resultados demonstrou que todas as empresas possuem a licença ambiental e o PGRS – Plano de Gerenciamento de Resíduos Sólidos – atualizados, conforme previsto na legislação. Os resultados mostram que as empresas avaliadas não realizam campanhas de conscientização para os consumidores, bem como não possuem iniciativas de instalação de pontos de coleta ou acordos com fornecedores para recolhimento de embalagens. A logística reversa de embalagens é observada somente na empresa V4, sendo também a única com investimento em cooperativas ou associação de catadores. Com base nestes dados, sugeriu-se a implantação de um sistema de logística reversa que envolva os consumidores, atendendo à legislação vigente
Keywords: Gestão ambiental; Sustentabilidade; Indústria vinícola - Vale dos Vinhedos, Região (RS); Reaproveitamento (Sobras, refugos, etc.); Environmental management; Sustainability; Wine industry - Vale dos Vinhedos, Região (Brazil); Recycling (Waste, etc.)